2017
DOI: 10.1534/g3.116.036038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes MediatingDrosophilaFollicle Cell Progenitor Differentiation by Screening for Modifiers of GAL4::UAS Variegation

Abstract: The Drosophila melanogaster ovarian follicle cell lineage provides a powerful system for investigating how epigenetic changes contribute to differentiation. Downstream from an epithelial stem cell, follicle progenitors undergo nine mitotic cell cycles before transitioning to the endocycle and initiating differentiation. During their proliferative phase, follicle progenitors experience Lsd1-dependent changes in epigenetic stability that can be monitored using GAL4::UAS variegation. Eventually, follicle progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Variegated GFP expression, due to a heterogeneous activation of the transgene, was observed for several driver/reporter pairs in FSCs (Skora and Spradling 2010; Lee et al 2017). When co-expressing the replicon and the VSR CrPV-1A in mutant backgrounds that dominantly suppress variegation, similar patches were observed (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…Variegated GFP expression, due to a heterogeneous activation of the transgene, was observed for several driver/reporter pairs in FSCs (Skora and Spradling 2010; Lee et al 2017). When co-expressing the replicon and the VSR CrPV-1A in mutant backgrounds that dominantly suppress variegation, similar patches were observed (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…See text for details. References cited in the table: (1) ( Yan et al 2014 ; Sanchez et al 2016 ) (2) ( Mummery-Widmer et al 2009 ; Saj et al 2010 ; Neumüller et al 2011 ) (3) ( Mummery-Widmer et al 2009 ; Saj et al 2010 ; Neumüller et al 2011 ) (4) ( Yan et al 2014 ; Sanchez et al 2016 ) (5) ( Lindquist et al 2011 ) (6) ( Chauvin et al 2014 ) (7) ( Yu et al 2016 ) Others compared but no overlap found: (8) ( Jia et al 2015 ; Lee et al 2017b ) (9) ( Jia et al 2015 ; Lee et al 2017b ) (10) ( Mummery-Widmer et al 2009 ; Saj et al 2010 ; Neumüller et al 2011 ) …”
Section: Resultsmentioning
confidence: 99%
“…We compared these 24 genes to orthologs identified in large-scale RNAi screens in Drosophila for genes regulating GSCs in the fly ovary ( Yan et al 2014 ; Sanchez et al 2016 ) and testis ( Yu et al 2016 ), and in follicle stem cells (FSCs) ( Jia et al 2015 ; Lee et al 2017b ). We found orthologs of 6 genes ( cye-1 , eif-6 , gsk-3 , mcm-7 , nxt-1 , rps-8 , teg-4 ) in common (none of our genes were identified in the screens for FSC regulation).…”
Section: Resultsmentioning
confidence: 99%
“…USP36 is a deubiquitinase demonstrated to promote RNA polymerase I stability for the ribosomal RNA processing and translation 85 . Previous studies found that the scny D. melanogaster homologue also acts as a histone H2B ubiquitin protease 86 . The atrophic ovary in the knockdown shows that the ribosomal RNA translation and/or the chromatin modification function may affect oocyte or ovarian development in addition to its role in embryogenesis 85 .…”
Section: Discussionmentioning
confidence: 99%